Jurug Woodland Zoo( Redesain Taman Satwa Taru Jurug dengan Pendekatan Ruang Terbuka pada Ruang Habitat Satwa) - Anugrahani, Nur; , Ir. Indrawati, MT (2016)
Indonesia is a country that has a tropical climate and culture that is diverse, so lots of tourists come for a vacation to Indonesia. Tourism in Indonesia is very attractive from natural as well as artificial Indonesia deserves to become tourist destinations. Indonesia has a diverse culture, tribes and languages, so in Indonesia has a variety of local wildlife in conservation or not. Indonesia has an artificial recreation attractions or education such as zoos, but zoos in Indonesia from 58, 29 only zoo which is pretty decent, and 4 of them have accredited A or feasible in accordance with standards such as the Garden Safari Prigen, East Java, West Java Cisarua Safari Park, Safari Park in Gianyar, Bali, and Sea World Ancol Jakarta, this coverage is more to safari. Zoo in Indonesia one of the TSTJ who are in Solo, the Zoo in TSTJ is one of the oldest zoos in Indonesia but the lack of a treatment so that the Zoo is not worth it anymore. Although Solo is a town of MICE where to tour, then an awful lot of tough tour on hotels, restaurants, as well as some souvenirs. Thus a lack of open space for masayarakat for leisure or relaxation in comfort. Solo only had 12% RTH, whereas RTH needs to Solo at least 30%, thus the existence of open space or open space as well as RTH in the city of Solo. The area of Riau Province is an area for the benefit of the environment so that at the Zoo in Jurug is required for RTH as well as open space on space habitat wildlife so that it complies with the standards of their Habitat in natural on open space, as well as provide the comfort of visitors to leisure as well as education in TSTJ.